El estereotipo invisible: imágenes del afrodescendiente en la narrativa argentina del siglo XIX (Altre Modernità, 2011)
This paper deals with different images of Black minorities inArgentinian Literature during XIX th. century. At first, Afrodescendants numbered almost 25 % of the population. However, in comparison with other ethnic groups, such as the "gauchos",there are not literary works mainly concerned with Afroargentinian people. They only appear as secondary characters and they are reduced to one or two common places: the loyal servant o the brave soldier, for instance.Ideological motivs could explain this absence. In fact, Black peoplewere exluded from a political agenda created by criollistintellectuals from the historical origins of the Nation.